Brassinosteroid Signaling, Crosstalk and, Physiological Functions in Plants Under Heavy Metal Stress - Kour, Jaspreet; Kohli, Sukhmeen Kaur; Khanna, Kanika; Bakshi, Palak; Sharma, Pooja; Singh, Arun Dev; Ibrahim, Mohd; Devi, Kamini; Sharma, Neerja; Ohri, Puja; Skalicky, Milan; Brestic, Marian; et al. (Frontiers in Plant Science, 2021)
Brassinosteroids (BRs) are a novel group of plant steroidal hormones that modulate developmental processes and help in stress management. Biosynthesis of BRs takes place through established early C-6 and late C-6 oxidation pathways and the C-22 hydroxylation pathway triggered by activation of the DWF4 gene which acts on multiple intermediates. BRs are recognized at the cell surface by the receptor kinases, BRI1 and BAK1, which relay signals to the nucleus through a phosphorylation cascade involving phosphorylation of BSU1 protein and proteasomal degradation of BIN2 proteins. Inactivation of BIN2 allows BES1/BZR1 to enter the nucleus and regulate the expression of target genes. In the whole cascade of signal recognition, transduction and regulation of target genes, BRs crosstalk with other phytohormones that play significant roles. In the current era, plants are continuously exposed to abiotic stresses and heavy metal stress is one of the major stresses. The present study reveals the mechanism of these events from biosynthesis, transport and crosstalk through receptor kinases and transcriptional networks under heavy metal stress.